Akkermansia muciniphila: biology, microbial ecology, host interactions and therapeutic potential - Ioannou, Athanasia; Berkhout, Maryse D.; Geerlings, Sharon Y.; Belzer, Clara (Nature reviews. Microbiology, 2025)
Akkermansia muciniphila is a gut bacterium that colonizes the gut mucosa, has a role in maintaining gut health and shows promise for potential therapeutic applications. The discovery of A. muciniphila as an important member of our gut microbiome, occupying an extraordinary niche in the human gut, has led to new hypotheses on gut health, beneficial microorganisms and host–microbiota interactions. This microorganism has established a unique position in human microbiome research, similar to its role in the gut ecosystem. Its unique traits in using mucin sugars and mechanisms of action that can modify host health have made A. muciniphila a subject of enormous attention from multiple research fields. A. muciniphila is becoming a model organism studied for its ability to modulate human health and gut microbiome structure, leading to commercial products, a genetic model and possible probiotic formulations. This Review provides an overview of A. muciniphila and Akkermansia genus phylogeny, ecophysiology and diversity. Furthermore, the Review discusses perspectives on ecology, strategies for harnessing beneficial effects of A. muciniphila for human mucosal metabolic and gut health, and its potential as a biomarker for diagnostics and prognostics. In this Review, Belzer and colleagues explore the diversity of the gut bacterium Akkermansia muciniphila , its biological functions and interactions with the host, diet and other members of the microbiota, as well as its association with health and disease and its potential in various applications.